Development of Kalipasang Tourism as Sustainable Ecotourism at the Kopeng Resort, Mount Merbabu National Park - Hermawan, Bagus; Ashila, Jilan; Febrian, Ardhitya Rio; Safitri, Fauziana Erlis; Ramadhan, Auriga Wahyu Widyadana; Sunarhadi, Muhammad Amin (Journal of Geography Science and Education, 2023)
Kalipasang is one of the tours in the Kopeng Resort area which has the appeal of pine stands and campgrounds. This tour is part of the Kopeng Resort which is in the Mount Merbabu National Park area which has been extensively developed. However, good tourism is tourism that can boost the economy, have benefits for the community, and maintain the environment. Therefore, the purpose of this research is to find out the appropriate strategies to do so that Kalipasang tourism can be optimal as a sustainable ecotourism. The data collection method was carried out by means of field observations and interviews. The data processing method uses an analysis of the basic principles of ecotourism, IFAS and EFAS, SWOT, and sustainable ecotourism modelling. The results of this study indicate that the strategy for developing Kalipasang tourism as a sustainable ecotourism can be seen in 3 aspects, namely economic, social and environmental. From an economic aspect, it is necessary to improve facilities, carry out promotions, and make ticket prices competitive. Meanwhile, from a social aspect, it is necessary to have community participation in tourism development, efforts to educate tourists, and involve stakeholders. Meanwhile, in terms of environmental aspects, efforts to conserve plants or animals and good waste management are needed. With the combination of these three aspects, Kalipasang tourism as sustainable ecotourism can be developed.